I-KID study protocol: evaluation of efficacy, outcomes and safety of a new infant haemodialysis and ultrafiltration machine in clinical use: a randomised clinical investigation using a cluster stepped-wedge design - Shriya Sharma; Heather J Lambert; John N S Matthews (BMJ Publishing Group, 2021)
Introduction The I-KID study aims to determine the clinical efficacy, outcomes and safety of a novel non-CE-marked infant haemodialysis machine, the Newcastle Infant Dialysis Ultrafiltration System (NIDUS), compared with currently available therapy in the UK. NIDUS is specifically designed for renal replacement therapy in small babies between 0.8 and 8 kg.Methods and analysis The clinical investigation is taking place in six UK centres. This is a randomised clinical investigation using a cluster stepped-wedge design. The study aims to recruit 95 babies requiring renal replacement therapy in paediatric intensive care units over 20 months.Ethics and dissemination The study has high parent and public involvement at all stages in its design and parents will be involved in dissemination of results to parents and professionals via publications, conference proceedings and newsletters. The study has has ethics permissions from Tyne and Wear South Research Ethics Committee.Trial registration numbers IRAS ID number: 170 481MHRA Reference: CI/2017/0066ISRCT Number: 13 787 486CPMS ID number: 36 558NHS REC reference: 16/NE/0008Eudamed number: CIV-GB-18-02-023105Link to full protocol v6.0: https://fundingawards.nihr.ac.uk/award/14/23/26